Mycobacterial Arthritis and Synovitis in Painted Reed Frogs (Hyperolius marmoratus). Issue 2 (February 2017) - Barrows, M.; Koeppel, K.; Michel, A.; Mitchell, E.
Summary: Several species of atypical mycobacteria have been isolated from wild and captive amphibians. In captive anurans, cutaneous and visceral mycobacteriosis are common and can result in significant mortality, particularly when animals are immunocompromised. Mycobacterial arthritis and synovitis are reported rarely in amphibians. We describe 20 cases in painted reed frogs ( Hyperolius marmoratus ), which presented with cachexia, limb paresis or paralysis or 'spindly leg syndrome'. Histopathology revealed multifocal histiocytic to granulomatous synovitis affecting appendicular, rib or spinal intervertebral joints. Periarticular granulomata, granulomatous cellulitis and skeletal muscle atrophy, necrosis and degeneration were also present. In one case, granulomatous spinal osteomyelitis was recorded. Ziehl–Neelsen stains showed large numbers of acid-fast bacteria in macrophages and histiocytes. The mycobacterial isolates obtained from culture were identified as members of the Mycobacterium chelonae complex (either M. chelonae or Mycobacterium abscessus ). This was confirmed by 5′-16S ribosomal ribonucleic acid (rRNA) sequencing. In 17 cases mycobacterial lesions were present only in the joints and skeleton, highlighting the importance of not ruling out mycobacterial infection on the basis of absence of cutaneous or visceral lesions.